Alteration in endometrial helper T‐cell subgroups in chronic endometritis. (25th November 2020) - Kitazawa, Jun; Kimura, Fuminori; Nakamura, Akiko; Morimune, Aina; Hanada, Tetsuro; Amano, Tsukuru; Tsuji, Shunichiro; Kasahara, Kyoko; Satooka, Hiroki; Hirata, Takako; Kushima, Ryoji; Murakami, Takashi
Abstract: Problem: The effect of chronic endometritis (CE) on the subpopulation of CD4 + T cells, Th1, Th2, Th17, and regulatory T cells in the endometrium is unknown. Method of study: Lymphocytes were isolated from the endometrium of CE patients ( n  = 12) and non‐CE patients ( n  = 7). The CD4 + T‐cell profile was analyzed by flow cytometry and immunofluorescence. Results: In the endometrium of CE patients, there were significantly more Th1 cells among CD4 + cells and fewer Th2 cells in comparison to non‐CE patients. No marked difference was observed in Th17 cells or Foxp3 + Treg cells. Moreover, the proportion of Th1 cells increased and the proportion of Th2 cells decreased as the number of CD138 + cells increased. Furthermore, when the localization of CD138 + cells and CD4 + cells was examined, CD4 + cells were found to be clustered around CD138 + cells in CE patients. Conclusion: The CD4 + T‐cell profile in the endometrium is altered in women with CE. This finding may help to clarify the pathophysiology and development of treatment methods for CE.